Multi-thread-based probabilistic security analysis model calculation speed increasing method - WANG ZHENQI; ZHANG JUN; TAO YINYONG; YE TIANBO; MA GANG; WANG ZIHU (2024)
The invention particularly relates to a multithreading-based probabilistic security analysis model calculation speed increasing method, which comprises the following steps of: splitting a probabilistic security analysis model into a plurality of sub-cases according to a case splitting basis of the probabilistic security analysis model; performing simultaneous calculation on each sub-case to obtain a calculation result of each sub-case; and summing the calculation results of the sub-cases to obtain the calculation result of the split probabilistic safety analysis model. According to the multi-thread-based probabilistic security analysis model calculation speed increasing method, the calculation speed of the probabilistic security analysis model is greatly increased on the premise that the precision of the probabilistic security analysis model is not reduced. 本发明具体涉及一种基于多线程的概率安全分析模型计算速度提升方法，包括如下步骤：根据概率安全分析模型案例拆分依据，将概率安全分析模型拆分为多个子案例；对各个子案例进行同时计算，得到各个子案例的计算结果；将各个子案例的的计算结果加和，得到拆分后概率安全分析模型计算结果。本发明的基于多线程的概率安全分析模型计算速